Tantangan Implementasi Peraturan Daerah tentang Kawasan Tanpa Rokok di Tatanan Perkantoran di Kabupaten Dharmasraya - Despariyenita, Despariyenita; Lestari, Yuniar; Ernawati, CH. Tuti (FORIKES, 2024)
Dharmasraya Regency has established a smoke-free area in office settings, but many employees still smoke, so that the community does not implement the policy. The purpose of the study was to determine the implementation of the smoke-free area regional regulation in office settings in Dharmasraya Regency. This study used mixed methods. Data collection was carried out by distributing questionnaires to 130 respondents, interviewing 8 informants and discussions in 2 groups to determine the implementation of the smoke-free area regional regulation according to aspects of communication, resources, disposition and bureaucratic structure. The results of the quantitative analysis showed that most respondents had good knowledge and positive attitudes, but there were still violations. The smoke-free area regional regulation was socialized only once in the early stages, so that communication regarding the delivery of the regulation was cut off and the program did not continue. There had been no commitment or consistency from the leadership, there had been no information media related to the regulation, there had been no application of sanctions for violators, and there had been no evaluation. It was concluded that the smoke-free area policy was not continued, not socialized and not handed over.Keywords: smoke-free area; regional regulation; implementation ABSTRAK Kabupaten Dharmasraya telah menetapkan kawasan tanpa rokok di tatanan perkantoran, tetapi masih banyak pegawai yang merokok, sehingga masyarakat tidak menerapkan kebijakan tersebut. Tujuan penelitian adalah mengetahui implementasi peraturan daerah kawasan tanpa rokok di tatanan perkantoran di Kabupaten Dharmasraya. Penelitian ini menerapkan mix methods. Pengumpulan data dilakukan dengan menyebarkan kuesioner kepada 130 responden, mewawancarai 8 informan dan diskusi dalam 2 kelompok untuk mengetahui implementasi peraturan daerah kawasan tanpa rokok menurut aspek komunikasi, sumber daya, disposisi dan struktur birokrasi. Hasil analisis kuantitatif menunjukkan bahwa sebagian besar responden memiliki pengetahuan baik dan sikap positif, namun masih ada pelanggaran. Peraturan daerah kawasan tanpa rokok disosialisasikan hanya sekali pada tahap awal, sehingga komunikasi penyampaian peraturan terputus dan program tidak berlanjut. Belum ada komitmen atau konsistensi dari pimpinan, belum ada media informasi terkait peraturan, belum ada penerapan sanksi bagi pelaku pelanggaran, dan belum ada evaluasi. Disimpulkan bahwa kebijakan kawasan tanpa rokok tidak dilanjutkan, tidak disosialisasikan dan tidak diserahterimakan. Kata kunci: kawasan tanpa rokok; peraturan daerah; implementasi